2017
DOI: 10.5152/tud.2017.14478
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of platelet to lymphocyte and neutrophil to lymphocyte ratio in determining urethral stricture after transurethral resection of prostate

Abstract: Objective: The pathology of urethral stricture disease is still unclear however progressive inflammation may contribute to the development of urethral stricture. The platelet-to-lymphocyte ratio (PLR) is a new and simple marker that indicates inflammation. In this study we aimed to investigate the predictive value of neutrophil to lymphocyte ratio (NLR) and PLR in patients with urethral stricture who underwent transurethral resection of prostate (TURP). Material and methods:A total of 208 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…As such, the NLR has been reported to be a significant marker for patient counseling and clinical trial design (21). In a related study of 208 patients with a history of urethral stricture after transurethral resection of the prostate from our country, it was shown that the NLR was relatively higher in relapsed patients but not significant (9). In our study, there were no statistically significant differences between neutrophils, lymphocytes, NLR, and patients with and without stricture recurrence after urethroplasty.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As such, the NLR has been reported to be a significant marker for patient counseling and clinical trial design (21). In a related study of 208 patients with a history of urethral stricture after transurethral resection of the prostate from our country, it was shown that the NLR was relatively higher in relapsed patients but not significant (9). In our study, there were no statistically significant differences between neutrophils, lymphocytes, NLR, and patients with and without stricture recurrence after urethroplasty.…”
Section: Discussionmentioning
confidence: 90%
“…When urethral strictures are considered, fibroblasts are probably responsible for the development of the urethral stricture; however, the reason for the urethral stricture is related to the urinary extravasation into the subepithelial space causing increased inflammation and subsequent scar formation. With this knowledge, many authors have used colchicine, mitomycin-C, triamcinolone, corticosteroids, and anti-inflammatory drugs locally or systemically to reduce urethral stricture after urethral procedures (9). In this context, urethral stricture is a result of inflammatory changes in the epithelium of the urethra and can be treated by interfering with the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…NLR and PLR are inconsistent in their ability to predict urethral stricture behavior but given the ease of collection of these markers, further evaluation may be warranted. 58,60 In addition, degree of pelvic trauma is not consistently associated with urethral stricture formation. 47 Further investigation is needed, given the potential for bladder dysfunction and subsequent renal failure as well as the patient morbidity associated with repeated surgeries following failure of initial management.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The plasma neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are nonspecific markers of systemic inflammation. [58][59][60] Given that platelet, neutrophil, and lymphocyte counts are often included as routine lab work for patients, there has been significant interest in evaluating these markers in the setting of urethral strictures. 58,60 One study demonstrated higher absolute neutrophil count and NLR in subjects with recurrent urethral stricture after undergoing DVIU, suggesting that chronic inflammation may contribute to stricture recurrence.…”
Section: Contribution Of the Innate Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation